Monophasic electrical stimulation produces high rates of adverse skin reactions in healthy subjects. - Fary, Robyn; Briffa, Kathy (Taylor and Francis, 2011)
Monophasic pulsed electrical stimulation (PES) has been reported to improve pain and function in osteoarthritis of the knee with few side effects. This use of monophasic current is contrary to conventional thinking where it is often associated with adverse skin reactions. The objectives of this study were to compare the rates of adverse skin reactions, using independently developed subsensory monophasic PES in healthy subjects, with those described in previous studies and compare the rate of adverse skin reactions after using the monophasic PES with that after using the same shaped electrical waveform that is asymmetrically biphasic. Healthy subjects (n=25) with no contraindications to electrical stimulation were administered subsensory, monophasic, and biphasic PES sequentially to the knee region for approximately 10 minutes each. Stimulation intensities; duration of stimulation; description of sensation reported; skin condition after intervention; and duration of skin reaction were all recorded. Fifty-two percent of subjects experienced adverse skin reactions using monophasic PES. This was significantly different from the reported rates in three of the four previous studies (p<0.04). Only one subject (4%) using the biphasic current demonstrated an adverse skin reaction. Results support the caution advised in the electrotherapy literature when using monophasic electrical stimulation.